2015
DOI: 10.1186/s13068-015-0284-1
|View full text |Cite
|
Sign up to set email alerts
|

Discovery of the combined oxidative cleavage of plant xylan and cellulose by a new fungal polysaccharide monooxygenase

Abstract: BackgroundMany agricultural and industrial food by-products are rich in cellulose and xylan. Their enzymatic degradation into monosaccharides is seen as a basis for the production of biofuels and bio-based chemicals. Lytic polysaccharide monooxygenases (LPMOs) constitute a group of recently discovered enzymes, classified as the auxiliary activity subgroups AA9, AA10, AA11 and AA13 in the CAZy database. LPMOs cleave cellulose, chitin, starch and β-(1 → 4)-linked substituted and non-substituted glucosyl units of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
189
1
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 198 publications
(199 citation statements)
references
References 41 publications
(59 reference statements)
8
189
1
1
Order By: Relevance
“…Oligosaccharides released and not released refers to + and −, respectively a Data from Frommhagen et al [ 2 ] b Gluco-oligosaccharides oxidized at the C1 (GlcOS n # ) or C4 position (GlcOS n *) c Xylo-oligosaccharides oxidized at the C1 (XOS n # ) or C4 position (XOS n *) d Regenerated amorphous cellulose (RAC) e Xyloglucan from tamarind seed, β-(1 → 3, 1 → 4)-glucan from barley and β-(1 → 3, 1 → 4)-glucan from oat spelt f Oat spelt xylan (OSX), birchwood xylan (BiWX), wheat arabinoxylan (WAX) g β-(1 → 4)-linked gluco- and xylo-oligosaccharides, degree of polymerization 2–5…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Oligosaccharides released and not released refers to + and −, respectively a Data from Frommhagen et al [ 2 ] b Gluco-oligosaccharides oxidized at the C1 (GlcOS n # ) or C4 position (GlcOS n *) c Xylo-oligosaccharides oxidized at the C1 (XOS n # ) or C4 position (XOS n *) d Regenerated amorphous cellulose (RAC) e Xyloglucan from tamarind seed, β-(1 → 3, 1 → 4)-glucan from barley and β-(1 → 3, 1 → 4)-glucan from oat spelt f Oat spelt xylan (OSX), birchwood xylan (BiWX), wheat arabinoxylan (WAX) g β-(1 → 4)-linked gluco- and xylo-oligosaccharides, degree of polymerization 2–5…”
Section: Resultsmentioning
confidence: 99%
“…Masses of lithium-adducted C1- or C4-oxidized gluco-oligosaccharides for RAC incubated with Mt LPMO9B or Mt LPMO9C, respectively, were determined and assigned as described previously [2]. …”
Section: Methodsmentioning
confidence: 99%
“…It has previously been shown that certain LPMOs can cleave xylan, only if the xylan is complexed with cellulose [23]. In order to gain further insight into the potential role of FgLPMO9A in plant cell wall degradation, we mixed cellulose (PASC) with different hemicelluloses and treated the resulting polysaccharide mixtures with FgLPMO9A, in the presence or absence of ascorbic acid as electron donor.…”
Section: Activity On Mixtures Of Hemicelluloses and Pascmentioning
confidence: 99%
“…LPMOs cleave polysaccharides while oxidizing one of the new chain ends at the C1 or C4 position, thus contributing to substrate depolymerization while increasing accessibility of the substrate to conventional GHs [12,15,17,18]. Since their discovery in 2010 [12], LPMOs with preference for various plant polysaccharides, such as cellulose [19,20], xyloglucan and other (1,4)-linked β-glucans [21], starch [22] and xylan [23] have been identified. LPMOs have become an…”
Section: Introductionmentioning
confidence: 99%
“…Lytic polysaccharide monooxygenases are copperdependent enzymes that use molecular oxygen and an external electron donor to cleave glycosidic bonds in various polysaccharides, such as cellulose [26,27], hemicelluloses [28,29], and chitin [30]. These enzymes are assigned into auxiliary activity (AA) families 9, 10, 11, and 13 in the CAZy database.…”
Section: Abstract: Aa13;mentioning
confidence: 99%